Между книжностью и разговорностью: малые фольклорные жанры в структуре метариторической рефлексии Достоевского - Анастасия Векшина (Napis, 2018)
The article presents an analysis of small forms of folklore (proverbs, sayings) in the structure of meta-rhetorical and meta-stylistic reflection of characters and narrators of F. Dostoevsky. It demonstrates the way in which Dostoevsky makes use of genre schemata, as well as words accepted in written and spoken language, transforming proverbs and giving them a new meaning depending on the context, as well as developing them within the framework of the plot (a proverb becomes the origin of an event in a novel or short story). The author of the article describes the mechanisms or re-interpretation, ostranenie, theatralisation, and irony, built on the basis of a certain deconstruction of fixed stylistic forms, which operate in written and spoken language. Using these ‘minor’ processes of linguistic transformation as an example, the article allows one to trace the general poetics strategy of the writer. The strategy is directed towards a renewal of literary language through, among other things, a confrontation with language that is colloquial, contemporary, devoid of ‘dead’ literary phraseology, and drawing from the wealth of creative folk imagination.